Do native-born bilinguals in the US earn more? - Chiswick, B.; Miller, Paul (Springer, 2017)
This paper uses the pooled data from 2005 to 2009 American Community Survey to analyze the economic benefits associated with bilingualism for adult men born in the United States. Bilingualism among the native born is defined as speaking a language at home other than or in addition to English. Native born bilingualism is rare; only 6.5% report a non-English language, and of those 71% report Spanish. Most of the native-born bilinguals report speaking English “very well” (85%), with most of the others speaking it “well” (10%). Other variables the same, overall bilinguals earn 4.7% less than monolingual English speakers, but the earnings differential varies sharply by the language spoken. Those who speak Native American languages, Pennsylvania Dutch and Yiddish have very low earnings due to a tendency to live in geographic or cultural enclaves. Spanish speakers earn 20% less than the monolingual English speakers overall, and other variables the same, have statistically significant 7% lower earnings. On the other hand, those who speak certain Western European and East Asian languages and Hebrew earn significantly more than monolingual English speakers.